2019
DOI: 10.1590/0034-7167-2018-0787
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between elderly stroke patient caregivers scale and nursing diagnoses

Abstract: Objective: To describe relationships between the ECPICID-AVC scale factors and the NANDA-I domains, classes, and Nursing Diagnoses (NDs). Method: Cross-mapping study between the NANDA-I taxonomy and ECPICID-AVC scale was constructed based on the eight ECPICID-AVC scale factors and the 13 NANDA-I domains. A descriptive analysis was performed to present the mapped elements. Results: Areas of similarity and intersection were found between the eight ECPICID-AVC factors and nine NANDA-I domains, 19 classes, and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In this study, it seems that the frequency of diagnosis related to physical mobility was high as stroke, paraplegia/tetraplegia, and hemiplegia patients accounted for 80%. In this regard, a previous study also reported that "impaired physical mobility" was a common nursing diagnosis for patients with cerebral vascular disease, and it was included as a necessary nursing diagnosis for stroke patients in previous studies (Granel and Bernabeu-Tamayo, 2020;McGlinchey et al, 2020;Pizzol et al, 2019). The high frequency of these nursing diagnoses is justified by the fact that cerebrovascular disease is a motor neuron disease that can lead to loss of voluntary movement control.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, it seems that the frequency of diagnosis related to physical mobility was high as stroke, paraplegia/tetraplegia, and hemiplegia patients accounted for 80%. In this regard, a previous study also reported that "impaired physical mobility" was a common nursing diagnosis for patients with cerebral vascular disease, and it was included as a necessary nursing diagnosis for stroke patients in previous studies (Granel and Bernabeu-Tamayo, 2020;McGlinchey et al, 2020;Pizzol et al, 2019). The high frequency of these nursing diagnoses is justified by the fact that cerebrovascular disease is a motor neuron disease that can lead to loss of voluntary movement control.…”
Section: Discussionmentioning
confidence: 98%